Implementing evidence‐based strategies for men with biochemically recurrent and advanced prostate cancer: Consensus recommendations from the US Prostate Cancer Conference 2024 - Bryce, Alan H.; Agarwal, Neeraj; Beltran, Himisha; Hussain, Maha H.; Sartor, Oliver; Shore, Neal; Antonarakis, Emmanuel S.; Armstrong, Andrew J.; Calais, Jeremie; Carducci, Michael A.; Dorff, Tanya Barauskas; Efstathiou, Jason A.; et al. (Cancer, 2025)
Current US clinical practice guidelines for advanced prostate cancer management contain recommendations based on high‐level evidence from randomized controlled trials; however, these guidelines do not address the nuanced clinical questions that are unanswered by prospective trials but nonetheless encountered in day‐to‐day practice. To address these practical questions, the 2024 US Prostate Cancer Conference (USPCC 2024) was created to generate US‐focused expert clinical decision‐making guidance for circumstances in which level 1 evidence is lacking. At the second annual USPCC meeting (USPCC 2024), a multidisciplinary panel of experts convened to discuss ongoing clinical challenges related to 5 topic areas: biochemical recurrence; metastatic, castration‐sensitive prostate cancer; poly [ADP‐ribose] polymerase inhibitors; prostate‐specific membrane antigen radioligand therapy; and metastatic, castration‐resistant prostate cancer. Through a modified Delphi process, 34 consensus recommendations were developed and are intended to provide clinicians who manage prostate cancer with guidance related to the implementation of novel treatments and technologies. In this report, the authors review the areas of consensus identified by the USPCC 2024 experts and evaluate ongoing unmet needs regarding translational application of the current clinical evidence. To address the nuanced questions related to prostate cancer management that are unanswered by prospective trials but nonetheless encountered in day‐to‐day practice, the US Prostate Cancer Conference (USPCC) generates US‐focused expert clinical decision‐making guidance for circumstances in which level 1 evidence is lacking. At the second annual USPCC meeting (USPCC 2024), a multidisciplinary panel of experts developed 34 consensus recommendations, which are intended to provide clinicians who manage prostate cancer with guidance related to the implementation of novel treatments and technologies.